Novel diagnostic and therapeutic approaches to malignant glioma (Swiss Medical Weekly, 2011)
Glioblastomas (World Health Organisation (WHO) grade IV) and anaplastic gliomas (astrocytomas, oligoastrocytomas, oligodendrogliomas) (WHO grade III) are collectively referred to as malignant gliomas. The diagnosis of malignant glioma may be suspected based on clinical history and neuroimaging findings, but histological confirmation remains the diagnostic “gold standard”. Molecular markers such as 1p/19q codeletion and isocitrate dehydrogenase (IDH) mutation provide important diagnostic and prognostic information. O–methylguanylmethyltransferase (MGMT) promoter methylation is another favourable prognostic marker and predicts benefit from alkylating agent chemotherapy in glioblastoma. Additionally, the extent of neurosurgical resection is a prognostic factor. Radiotherapy of the involved brain region or chemotherapy using the alkylating agent, temozolomide, are common therapeutic options for patients with anaplastic glioma. In contrast, temozolomide plus radiotherapy is the standard of care for most patients with glioblastoma. The increasing population of elderly patients with glioblastoma represents a particular challenge, with surgery followed by radiotherapy as the standard of care. Contemporary clinical studies focus on the role of angiogenesis. Specifically, pivotal phase III studies exploring the antibody to vascular endothelial growth factor (VEGF), bevacizumab, and the αvβ3/5 antagonist, cilengitide, in the management of newly diagnosed glioblastoma have completed enrolment. Moreover, a broad spectrum of other experimental treatment approaches, including immunotherapy with vaccines against glioma-associated antigens, are currently being explored in phase I/II clinical trials.